Bioassay-guided fractionation and identification of wound healing active compounds from Khaya senegalensis leaves - Akrimi Najihah Mohd Khamil; Norizamimie Nordin; Mohamad Afiq Aizuddin Rosdi; Mohamad Faiz Hamzah; Mohd Hasnan Mohd Noor; Siti Zuraidah Mohamad Zobir; Amyra Amat Sain; Mohammad Tasyriq Che Omar; Mohamad Nurul Azmi Mohamad Taib; Ayunni Salihah Zalaludin (PLoS ONE, 2026)
This study investigated the wound healing potential of Khaya senegalensis leaves through a comprehensive approach, including phytochemical, antioxidant, cytotoxicity, migration, and molecular docking analyses. Bioassay-guided isolation identified β-sitosterol and stigmasterol, with structures confirmed by NMR and FTIR analyses. Phytochemical screening revealed the presence of flavonoids, saponins, triterpenoids, tannins, and steroids, with solvent polarity significantly influencing composition. The ethyl acetate extract exhibited the strongest DPPH radical scavenging (IC₅₀ = 5.6 mg/mL). The methanol extract had the highest total phenolic content (198.8 mg GAE/g) while the ethyl acetate had the highest flavonoid content (1,228.1 mg QE/g). MTT assays confirmed the cytocompatibility of all extracts, fractions, and isolated compounds in HaCaT and HDF cells (>50% viability at ≤100 µg/mL). Scratch assays demonstrated significant, concentration-dependent wound closure, with optimal effects at 12.5 μg/mL. The most active fraction (1.2H) and subfractions (1.2.1H, 1.2.3H), as well as the isolated compounds, achieved complete wound closure in HDF cells within 24 hours. Molecular docking revealed strong binding of β-sitosterol and stigmasterol with TNF-α and GSK-3β, supporting their role in modulating inflammatory and proliferative pathways. These findings highlight Khaya senegalensis as a promising candidate for promoting wound repair, exerting antioxidant, cytocompatible, and pro-migratory effects.